ETANOL PRODUCTION FROM MENGKUDU FRUIT - Indrati Utami, Lucky (Jurnal Teknik Kimia, 2010)
Mengkudu represent all purpose crop, there is many product that could be developed fromroot, bar, leaf, and also it’s fruit. The mengkudu’s fruit have carbohydrate content as much as 51,67gr. With the existence of the carbohydrate rate, it enables to be used to produce ethanol. The aim ofthis research is to determine the best condition process to make an ethanol from raw material ofmengkudu’s fruit. Ethanol yielded to be obtained heatedly from mengkudu’s fruit liquid by using HCL0,4 N in three neck gourd as hydrolysis process, so that we got the sugar rate equal to 8,23%. Afterthat can be made ferment media from sugar liquid result of the hydrolysis and enhanced by a startervolume at spanning : 4- 12%. Later fermented as according to variation time of between 24 until 72hours. The liquid result of the ferment dissociated by distillation, and the temperature maintenance for80 ºC. The biggest result of ethanol rate obtained when ferment 60 clock, addition of volume starter10% with ethanol rate = 6,24 %.Key words : Ferment , Hydrolysis, Mengkudu , Saccharomyces Cerevisiae, Ethano